Perubahan Bisnis Menuntut SDM Professional - Prihatin Tiyanto PH (Universitas Wahid Hasyim, 2006)
The new competencies that are required in today’s human recources professionals and how one company has gone about the development of those competencies within its human resources community. Talent of human resource that will serve companies growing human resources needs of the other, university, professional association ought to play it’s the best practice in organization